Association of Cardiovascular Health Score Trajectory With Incident Myocardial Infarction in Hypertensive Patients. Issue 11 (9th September 2022) - Huang, Zegui; Chen, Zekai; Wang, Xianxuan; Ding, Xiong; Cai, Zefeng; Li, Weijian; Cai, Zhiwei; Lan, Yulong; Chen, Guanzhi; Fang, Wei; Wu, Shouling; Chen, Youren
Abstract : Background: The association between changes in cardiovascular health score (CHS) over time and myocardial infarction (MI) risk in hypertensive patients remains unclear. Method: This was a prospective study comprising 17 374 hypertensive patients from the Kailuan study cohort who underwent 3 surveys and were identified to be free of MI, stroke, or cancer from 2006 to 2010. CHS consisted of 7 cardiovascular health metrics (plasma glucose, total cholesterol, blood pressure, smoking, body mass index, physical activity, salt intake), ranging from 0 (worst) to 13 (best) in the study. CHS trajectories were developed during 2006 to 2010 to predict the MI risk from 2010 to 2020. Additionally, the Cox proportional hazard model was established to calculate the hazard ratio and 95% CI of incident MI in different trajectory groups. Result: This study identified the 5 CHS trajectories from 2006 to 2010: low-stable (n=1161; range, 4.7–4.5), moderate-decreasing (n=3928; decreased from 6.9 to 6.0), moderate-increasing (n=1014; increased from 5.6 to 7.8), high-stable I (n=7940; range, 8.1–8.2), and high-stable II (n=3331; range, 9.2–9.7). During the median follow-up of 10.04 years, 288 incident MI cases were identified. After adjusting for potential confounders, compared with low-stable group, the hazard ratio and 95% CI of MI were 0.24 (0.15–0.40) for high-stable II, 0.36 (0.24–0.54) for high-stable I, 0.46 (0.25–0.83) for moderate-increasing, and 0.61 (0.41–0.90) for moderate-decreasing, respectively. Conclusions: In hypertensive patients, high-stable CHS or improvement in CHS is associated with a lower risk of incident MI, when compared with low-stable CHS trajectory over time.